2017
DOI: 10.1111/agec.12355
|View full text |Cite
|
Sign up to set email alerts
|

Can flexible agricultural microfinance loans limit the repayment risk of low diversified farmers?

Abstract: Using a unique data set from a commercial microfinance institution in Madagascar, this article investigates the credit risk of microfinance loans with flexible repayment schedules for crop farmers. Flexible repayment schedules allow a redistribution of principal payments during periods with low agricultural returns to periods when agricultural returns are high through predefined grace periods. We apply propensity score matching to investigate how different numbers of grace periods reflecting different levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Financial attractiveness is the bargaining power of focal companies toward financial institutions when seeking to improve the financial performance of their upstream/downstream supply chain [55]. Recent literature has confirmed that it is the ability of microfinance institutions to provide desired loan amounts to small users [70]. As financial solutions in this context are not merely financially oriented, financial attractiveness is divided into that toward cooperative institutions and that toward customers in this research.…”
Section: Effect Of Financing Attractivenessmentioning
confidence: 95%
See 1 more Smart Citation
“…Financial attractiveness is the bargaining power of focal companies toward financial institutions when seeking to improve the financial performance of their upstream/downstream supply chain [55]. Recent literature has confirmed that it is the ability of microfinance institutions to provide desired loan amounts to small users [70]. As financial solutions in this context are not merely financially oriented, financial attractiveness is divided into that toward cooperative institutions and that toward customers in this research.…”
Section: Effect Of Financing Attractivenessmentioning
confidence: 95%
“…Second, Jiebei allows flexible repayment condition and loan amounts. The flexible repayment condition is the main reason why Microloans are an advantage [70]. Farmers usually only need short-term and small loans, for example, a one-thousand-yuan loan for 20 days.…”
Section: Effect Of Financing Attractivenessmentioning
confidence: 99%
“…Flexible loans are loans whose transactions can be reconciled with the cash flows of a borrower (Collins et al, 2009). For farmers, flexible loans allow repayments to be redistributed during periods of low returns to periods of high returns by offering predefined grace periods Weber and Musshoff (2017). Theoretically, the link between flexibility and access to credit is captured by a conceptual framework that posits that there will be a higher demand for loans when there is flexibility as farmers will appreciate that flexibility eases repayment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Microfinance institutions are some of the formal financial providers that have adopted flexible terms of lending in order to attract farmers to take up loans. However, only a few MFIs offer flexible loan contracts worldwide because they are considered risky (Labie et al, 2017;Weber and Musshoff, 2017). Field and Pande (2008) disagree with the view that flexible loans are risky, as they note that flexibility may actually lead to higher repayment rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation